Influence of affective auditory stimuli on balance control during static stance. Issue 3 (4th March 2017) - Chen, Xingyu; Qu, Xingda
Abstract: The main purpose of this study was to examine the effects of affective auditory stimuli on balance control during static stance. Twelve female and 12 male participants were recruited. Each participant completed four upright standing trials including three auditory stimuli trials and one baseline trial (ie no auditory stimuli). The three auditory stimuli trials corresponded to the pleasant, neutral and unpleasant sound conditions. Center of pressure (COP) measures were used to quantify balance control performance. It was found that unpleasant auditory stimuli were associated with larger COP amplitude in the AP direction compared to the rest testing conditions. There were no significant interaction effects between 'auditory stimuli' and gender. These findings suggested that some specificities presented by auditory stimuli are important for balance control, and the effects of auditory stimuli on balance control were dependent on their affective components. Practitioner Summary: Findings from this study can aid in better understanding of the relationship between auditory stimuli and balance control. In particular, unpleasant auditory stimuli were found to result in poorer balance control and higher fall risks. Therefore, to prevent fall accidents, interventions should be developed to reduce exposures to unpleasant sound.